2021
DOI: 10.1126/sciadv.abi4567
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing nanofabrication through thermomechanical nanomolding

Abstract: Thermomechanical nanomolding puts a wide range of materials combinations in reach for nanofabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…[21] This behavior is also seen during TMNM, where a small grain size feedstock requires a lower pressure for successful nanomolding compared to a large grain size or single crystal feedstock. The predicted length of the molded nanowire in 1D TMNM, L, is shown in Equation 1 [11] :…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] This behavior is also seen during TMNM, where a small grain size feedstock requires a lower pressure for successful nanomolding compared to a large grain size or single crystal feedstock. The predicted length of the molded nanowire in 1D TMNM, L, is shown in Equation 1 [11] :…”
Section: Discussionmentioning
confidence: 99%
“…Recently, thermomechanical nanomolding (TMNM), a technique whereby a bulk feedstock of a desired material is pressed through a nanoporous mold at elevated temperatures and pressures, has been shown to yield high aspect ratio, single crystal nanowires over wafer-scale distances. [11][12][13][14] TMNM is materialagnostic, having been shown to work for a wide variety of materials including metals, [11,15] alloys, [11] and intermetallics. [16,17] TMNM of 1D nanowires relies on initial grain reorientation near the base of the nanowire as the bulk feedstock enters the nanopores of the mold to the preferred growth direction, which minimizes the total surface energy and interfacial diffusion barrier along the mold walls.…”
Section: Introductionmentioning
confidence: 99%
“…In TMNM, a bulk material of interest is extruded through a nanoporous mold at elevated temperatures (approximately 0.5 T m , where T m is the material’s melting point in Kelvin) and pressures (higher than 100 MPa) . Nanowire growth during TMNM is driven by lattice and interfacial diffusion along the mold channels. Additionally, grain reorientation occurs at the base of the nanowire in order to minimize the interfacial energy between the crystal and mold surfaces, leading to the formation of single-crystalline wires with consistent growth orientation .…”
mentioning
confidence: 99%
“…We have recently developed a controlled and scalable nanofabrication method called thermomechanical nanomolding (TMNM) that holds promise for obtaining single-crystal nanostructures. TMNM exhibits high control over the size and aspect ratio of the nanowires.…”
mentioning
confidence: 99%
“…The nanowires’ length and diameter are limited practically by the mold dimensions, but there is no fundamental limit to these features. We have demonstrated that TMNM can be applied to a wide range of materials, including metals, alloys, and ordered phases. , The underlying mechanism of TMNM is based on diffusion, specifically on interface diffusion (see Figure S2 Supporting Information) for temperatures above ∼0.4 T M , where T M is the melting temperature of the material. Notably, functional nanostructures fabricated by TMNM include superconductors, topological insulators, semiconductors, and phase change materials .…”
mentioning
confidence: 99%